2009
DOI: 10.1111/j.1468-1293.2009.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different patterns of nonadherence on the outcome of highly active antiretroviral therapy in patients with long‐term follow‐up

Abstract: ObjectivesThe aim of the study was to evaluate the impact of different patterns of nonadherence on treatment outcomes in patients with long-term follow-up. MethodsThis cohort study included patients who began highly active antiretroviral therapy during 1996-1999, with the last follow-up in 2007. Adherence was evaluated every 2 months by monitoring of pharmacy refills and by using self-reports. Patients were considered nonadherent at a specific visit when less than 90% of the prescribed drugs had been taken. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…12 Knobel et al 13 found that only 33% of patients in their study were able to maintain an adherence level of at least 90% and in a study by Shuter et al, 7 patients experienced an average adherence rate of 73%. Several factors can impact a patient's adherence and persistence with antiretroviral therapy, including relationship with/trust in provider, 14 lack of social support, 14,15 regimen complexity, 16,17 and misunderstanding of the disease and drug treatment.…”
Section: Introductionmentioning
confidence: 87%
“…12 Knobel et al 13 found that only 33% of patients in their study were able to maintain an adherence level of at least 90% and in a study by Shuter et al, 7 patients experienced an average adherence rate of 73%. Several factors can impact a patient's adherence and persistence with antiretroviral therapy, including relationship with/trust in provider, 14 lack of social support, 14,15 regimen complexity, 16,17 and misunderstanding of the disease and drug treatment.…”
Section: Introductionmentioning
confidence: 87%
“…10,11 Since adherence is unstable in situations such as mental conditions 12 with erratic 13 and dynamic courses, 14,15 or is expressed in other forms, such as missed doses or as treatment interruptions, i.e. so-called "drug holidays", 16 early detection of non-adherence may prevent the development of ART resistance and treatment failure. 17 In Brazil, few studies have investigated the impact of substance use or depressive symptoms on adherence to ART.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results suggest that for stroke patients, non-specific pill adherence ≥90% of the time, and not ≥80% of the time, is the cutoff point significantly linked to favorable outcomes. Indeed, in earlier studies of adherence to therapy in HIV-infected patients, the cutoff point of good adherence was the conventional 80% cutoff [10,11,12], but this changed [13,14], after a landmark study showed that HIV-infected patients with 95% or greater adherence had superior outcomes than patients with lower levels of adherence, to the extent that the percentage of patients with a favorable outcome rose by 20% when adherence increased from 90–95% to 95–100% [15]. …”
Section: Discussionmentioning
confidence: 99%